A Citizenship of distinction in the open radio debates of Kampala - (:unkn) unknown (My University, 2013)
This article investigates practices of speech and sociability in open radio debatesin Kampala to decipher imaginaries of citizenship in contemporary Uganda. Inthese ebimeeza (‘round tables’ in Luganda, also called ‘people’s parliaments’)orators are engaged in practices of social distinction when compared to thosethey call the ‘common men’. These spaces of discussion reflect the importanceof education in local representations of legitimacy and morality, whether inBuganda ‘neotraditional’ mobilizations or Museveni’s modernist vision ofpolitics. The ebimeeza and the government ban imposed on them in 2009 reveal the entrenchment of the vision of a ‘bifurcated’ public sphere, the separation of asphere of ‘development’ and a sphere of ‘politics’, the latter being only accessibleto educated ‘enlightened’ individuals – despite the revolutionary discourse and theinstitutionalization of the Movementist ‘grassroots democracy’ model in 1986.
Keywords: African Research